2005
DOI: 10.1108/13527590510606325
|View full text |Cite
|
Sign up to set email alerts
|

Barnyard democracy in the workplace

Abstract: Purpose -This paper aims to illustrate the interesting parallels that exist between the social behavior of farm animals and work-teams as a means of offering a novel point of view from which to understand teams. Design/methodology/approach -The empirical literature on the social behavior of farm animals is used as a starting-point to identify the key factors that generate instability in social relationships and, as a result, demonstrate the existence of a dominance hierarchy. These factors are then analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Along the same line of reasoning, Einarsen et al (2003) posited that an imbalance of power between the parties reflecting the formal status hierarchy would predict who is likely to be victimized. The more that a victim is dependent on one for valued resources, the more susceptible the former is to negative acts from the latter (Aquino and Lamertz, 2004; Brotheridge and Keup, 2005; Simpson and Cohen, 2004). Hoel and Salin (2003, p. 204) observed that “The power imbalance may reflect formal power relationships, or may refer to perceptions of powerlessness resulting from the bullying process itself”.…”
Section: Patterns Of Targetingmentioning
confidence: 99%
“…Along the same line of reasoning, Einarsen et al (2003) posited that an imbalance of power between the parties reflecting the formal status hierarchy would predict who is likely to be victimized. The more that a victim is dependent on one for valued resources, the more susceptible the former is to negative acts from the latter (Aquino and Lamertz, 2004; Brotheridge and Keup, 2005; Simpson and Cohen, 2004). Hoel and Salin (2003, p. 204) observed that “The power imbalance may reflect formal power relationships, or may refer to perceptions of powerlessness resulting from the bullying process itself”.…”
Section: Patterns Of Targetingmentioning
confidence: 99%
“…shifting goals without informing the employee, withholding information, and work interference), or belittlement (e.g. criticisms, undervaluing work, and excluding individuals; Brotheridge and Keup, 2005). Meglich et al (2012) grouped workplace bullying behaviors into intentionally malicious verbal behaviors, such as crude remarks and threats, and intentionally malicious nonverbal behaviors such as sabotaging or stealing work output, which increase in cruelty over a six-month or longer duration.…”
Section: Defining Workplace Bullyingmentioning
confidence: 99%